The influence of work life balance towards job performance in private higher education institution (PHEI) / Noorlaila Yunus and Siti Musalmah Ahmad Fuad. - Yunus, Noorlaila; Ahmad Fuad, Siti Musalmah (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia., 2017)
Work-Life Balance (WLB) is an important factor that the Human Resource Management of private higher education Institution (PHEI) should concern about in order to gain high Job Performance in the institution. If there are WLB practices implemented by the university, the Human Resource Department (HRD) must always get feedback from the employees to continuously improve the WLB policy. This will benefit not just the employees but the most important to the PHEI by having a good productivities and high job performance employees. The result shows that most of the employees in the university have good social support from their colleagues at work place, friends and their families. This support have given them inspiration and motivation in doing their job properly and finally they might achieved high job performance. Even though the result were positive about the social support the employees receives, the top management including the HRD need to revise their policy of WLB especially other factors that can influenced the employees to optimized their efforts in doing their job